Fano fingerprints of Majoranas in Kitaev dimers of superconducting adatoms - Dessotti, F. A. [UNESP]; Ricco, L. S. [UNESP]; Marques, Y. [UNESP]; Machado, R. S. [UNESP]; Guessi, L. H. [UNESP]; Figueira, M. S.; Souza, M. de [UNESP]; Seridonio, A. C. [UNESP] (Elsevier B.V., 2016)
We investigate theoretically a Fano interferometer composed by STM and AFM tips close to a Kitaev dimer of superconducting adatoms, in which the adatom placed under the AFM tip, encloses a pair of Majorana fermions (MFs). For the binding energy Ji of the Cooper pair delocalized into the adatoms under the tips coincident with the tunneling amplitude t between them, namely Delta =t, we find that only one MF beneath the AFM tip hybridizes with the adatom coupled to the STM tips. As a result, a gate invariance feature emerges: the Fano profile of the transmittance rises as an invariant quantity depending upon the STM tips Fermi energy, due to the symmetric swap in the gate potential of the AFM tip. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Fano effect; Kitaev dimer; Superconducting adatoms; STM tip; AFM tip